Complete mitochondrial genome of Haematopus ostralegus (Charadriiformes: Haematopodidae). Issue 1 (1st January 2017) - Lee, Mu-Yeong; Jeon, Hey Sook; Choi, Yu-Seong; Joo, Sungbae; An, Junghwa
Abstract: The Eurasian oystercatcher ( Haematopus ostralegus ), Near Threatened in the IUCN red list, was designated classified endangered species II by the Ministry of Environment of Korea and a Natural Monument (No. 326) by the Cultural Heritage Administration of Korea. In this study, the complete mitochondrial genome (16, 798 bp) of H. ostralegus was determined for the first time, including 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 1 non-coding region. The overall base composition was A (31.4%), C (31.3%), G (13.8%), and T (23.5%), so the percentage of A and T (54.9%) was slightly higher than that of G and C. A phylogenetic analysis using concatenated mitogenomes revealed that the family Haematopodidae has a closer relationship with the family Recurvirostridae and H. ostralegus and H. ater clustered together. The results are expected to provide useful resources for species identification and further phylogenetic studies of genus Haematopus .